Potential cutaneous carcinogenic risk of exposure to UV nail lamp: A review. Issue 6 (25th June 2018) - Shihab, Nahla; Lim, Henry W.
Summary: The increased use of ultraviolet (UV) nail lamps in recent years has generated safety concerns of this device. A UV nail lamp is a source of artificial UVA radiation, often used to dry, harden, and cure the nails at home and in the salon. UVA radiation is known to be mutagenic and can cause damage to the DNA, resulting in cutaneous malignancy. Currently, there are only a few studies that have evaluated UV nail lamp irradiation and its potential carcinogenic risk. We review the literature on UV nail lamps, its safety, effect on nails and hands, and the potential role in increasing the risk of cutaneous malignancy. Based on available data, the carcinogenic risk is low; nonetheless, the use of a broad spectrum sunscreen with SPF >30 before UV nail lamp exposure is recommended.